Adaptive Input Shaper for Payload Swing Control of a 5-dof Tower Crane with Parameter Uncertainties and Obstacle Avoidance - S.M. Fasih ur Rehman; Z. Mohamed; A.R. Husain; L. Ramli; M.A. Abbasi; W. Anjum; M.H. Shaheed (Elsevier, 2024)
Volume 154